PREEKLAMPTİK VE NORMAL PLASENTADA ENDOTELYAL NİTRİK OKSİT SENTETAZ İMMÜNREAKTİVİTESİNİN İNCELENMESİ - MUTLU, Canan; KOYUTÜRK, Meral; KARPUZ, Vildan (Cerrahpaşa Medical Journal, 2019)
Background and Design.- This study aims to determine the endothelial nitric oxide synthase (eNOS) immunreactivity of fetal and maternal placentas in preeclamptic and normal individuals and to investigate the possible relationship with the uteroplacental changes in preeclampsia. Material and Methods.- In this study, placental and blood samples of 10 preeclamptic group and control group were determined according to values of blood pressure (>140/90mmHg) and presence of proteinuria in the last trimester of pregnancy. Paraffin blocks of maternal and fetal sides of preeclamptic and normal placental tissue samples were prepared. Sections stained with Hematoxylin-Eosin and histopathology changing was evaluated by light microscope. eNOS activation were examined in samples of placenta tissues by streptavidine-biotine immunohistochemical methods. Results.- Systolic and diastolic blood pressure and proteinuria, which are diagnostic criteria of preeclampsia, were found increase and statistically significant in preeclamptic group comparing with the control group. Spiral arterioles and decidual histopathologic changes in the placentas of preeclamptic group were observed on light microscope. eNOS immunlocalization was observed in the villous of syncytiotrophoblastic cells by immunohistochemical examination. Immunohistochemical results were evaluated by scoring system. There was no significant difference between immunohistochemical score values of fetal and maternal tissue samples of two groups. Mean immunohistochemical score (IHS) values of maternal tissue samples in preeclamptic group were significantly higher than the control group values (p>0.05), when fetal tissue samples were considered, score values of preeclamptic group were also higher than the control group (p>0.005), but it was not statistically significant (p>0.05). Conclusion.- In conclusion, increase of eNOS activity in syncytiotrophoblastic cells play a role in preeclampsia related with hemo-dynamic changes in fetoplacental circulation.